PENGARUH KEPUASAN KONSUMEN TERHADAP PERILAKU PEMBELIAN ULANG KONSUMEN PADA CAFÃ‰ DAN RESTO BANGI KOPITIAM DI KOTA PALU - Mas?ud, Anshar Rahman (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to determine and analyze simultaneous and partial influence of consumer satisfaction on repurchase behavior in Bang Kopitiam Café and Resto in Palu City. The type of research is quantitative. The population in this study involves consumers who have visited Bangi Kopitiam Café and Resto at least 2 times. Sampling technique is accidental method, with sample of 90 respondents. Data collection using questionnaires. Data analysis tool is multiple linear regressions method. The result shows that consumer satisfaction simultaneously and partially influence repurchase behavior of consumers in Bangi Kopitiam Café and Resto Palu City.